HISTOLOGICAL CHANGES IN THE LIVER IN VIRAL HEPATITIS B AND C - Khafizova Klarakhon Abdumannobovna; Kakhorova Karomatkhon Sovronbaevna (Scholar Express Journals, 2026)
Viral hepatitis B and C are among the most common causes of chronic liver diseases worldwide and remain a serious public health problem. These infections lead to progressive liver damage, which may result in fibrosis, cirrhosis, and hepatocellular carcinoma. Histological examination of liver tissue plays a crucial role in assessing the degree of inflammation, necrosis, and fibrotic changes caused by hepatitis B virus (HBV) and hepatitis C virus (HCV). This article analyzes the main histological alterations observed in the liver during viral hepatitis B and C, highlighting similarities and differences in pathological changes. Particular attention is given to inflammatory activity, hepatocellular degeneration, fibrosis progression, and architectural remodeling of liver tissue. The study emphasizes the importance of histological evaluation for disease staging, prognosis, and selection of appropriate therapeutic strategies.
Keywords: viral hepatitis B; viral hepatitis C; liver histology